COMPARATIVE EVALUATION OF PCR BASED AMPLIFICATION OF CONSERVED GENOMIC REGIONS FROM XANTHOMONAS ORYZAE PV ORYZAE (XOO) FOR RAPID AND SPECIFIC DETECTION FROM INFECTED PLANT SAMPLES - PRAMOD D,; KISHORE N,; NASARUDDIN, (International Journal of Pharma and Bio Sciences, 2015)
Bacterial leaf blight of rice caused by pathogen Xanthomonas oryzae pv oryzae is a serious pest leading to major loss of rice production world wide. Early detection of pathogen can help in taking necessary precautionary measures to avoid onset and spread of disease. Conventional methods of pathogen identification are laborious, time taking and give inconsistent results. Rapid molecular methods like 16s rDNA amplification can only identify Xanthomonas sp. without any differentiation between pathogenic and non-pathogenic Xanthomonads. A specific, rapid diagnostic tool with reproducible results requires targeting unique features of a pathogen. Amplification of 16S rDNA, 16S-23S rDNA intergenic spacer region and IS113 are evaluated in the present paper for rapid and specific detection of Xoo.